1989
DOI: 10.1142/s0217979289000890
|View full text |Cite
|
Sign up to set email alerts
|

The Microscopic Approach in the Theory of Superconductors With a Many-Component Order Parameter

Abstract: In terms of the generalized Bardeen-Cooper-Schrieffer model for a superconductor with degenerate orbital electron states, we derive a Ginzburg-Landau energy functional with a microscopic deciphering of the coefficients involved. The superconducting order parameter is separated out by expanding the wave function of a Cooper pair in the basis functions of crystal point group irreducible representations. It is shown that a many-component superconducting order parameter may arise from the degeneracy of the electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…Finally, we reduce P k into irreducible representations (IRs) of the original crystal point group. The gap functions should be zero, and thus, the gap nodes appear, if the corresponding IRs do not exist in the results of reductions [7,9,35]. Otherwise, the superconducting gap will open in general.…”
Section: Classification Theory Of Superconducting Gapmentioning
confidence: 99%
“…Finally, we reduce P k into irreducible representations (IRs) of the original crystal point group. The gap functions should be zero, and thus, the gap nodes appear, if the corresponding IRs do not exist in the results of reductions [7,9,35]. Otherwise, the superconducting gap will open in general.…”
Section: Classification Theory Of Superconducting Gapmentioning
confidence: 99%
“…Izyumov et al [13] proposed to use IRs of space groups for the description of oneelectron states coupled in a Cooper pair and showed that the above-mentioned direct connection between multiplicity and parity of a Copper pair may be violated if oneelectron states are characterize by the wave vector in symmetrical directions in a Brillouin zone. The space-group approach to the wavefunction of a Copper pair was further developed [14 to 16] by making use of the Pauli exclusion principle and of the Mackey theorem [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…In both planes, there are four IRs, A g , B g , A u , and B u since the coset group M k /T is isomorphic to the point group C 2h [33]. The results are summarized in Table III. Note that the gap functions should be zero, which means the appearance of gap nodes, if the corresponding IRs do not exist in the reduction ofP k [21][22][23]. The absence of A u in PP corresponds to the emergent horizontal line node of the recently proposed E 2u state in UPt 3 superconductors [24,[34][35][36].…”
mentioning
confidence: 99%
“…Such classification provides useful information in analyzing the nodal structure of various unconventional superconductors [20]. Also, another development of gap classification based on the space group symmetry [21][22][23][24] gives us the correct way to take into account small representations at Brillouin zone (BZ) boundary in non-symmorphic space groups [25,26]. T. Micklitz and M. R. Norman [24] demonstrated in the pioneering work that new types of * nomoto.takuya@scphys.kyoto-u.ac.jp symmetry-protected nodes can appear at the BZ boundary.…”
mentioning
confidence: 99%